Determinants of Iron Supplementation (Fe) Adherence among Pregnant Women at Puskesmas Sugio Lamongan - Diah Eko Martini; Heny Ekawati; Lilis Maghfuroh; Silvy Harmiadillah; Wahyu Retno Gumelar; Aizatun Nisa (Universitas Muhammadiyah Jember, 2021)
Background: Anaemia during gestation is a complication that often occurs in pregnant women. This condition can be controlled by providing iron (Fe) supplementation; therefore, the government has set a policy of minimum service standards for the coverage of 90 tablets of iron (Fe) supplementation for the period of pregnancy. However, Pregnant women's adherence to iron (Fe) supplementation is still low. The objective of this research was to determine the factors that influence pregnant women's adherence to iron (Fe) supplementation.Method: The design of this study used a cross-sectional study approach. The sample was used for all pregnant women who were recorded at the Sugio Lamongan Health Center on April 2021 totaling 36 respondents, the data was taken using a structured questionnaire and assessed using chi-square and Fisher's Exact Test.Result: The findings revealed that the majority of pregnant women (66.6 percent) were obedient in taking iron (Fe) supplements (PR=0.227) is a factor of pregnant women's adherence to taking iron (Fe) supplements.Conclusion: Therefore, all access that affects antenatal care services and follow-up ANC services is an important element to improve the Adherence of pregnant women in taking iron (Fe) supplementation.